Schiff-Base Thiadiazole-Modified Hydrogels: A Comprehensive Review of Biomedical Applications - Muslah, Safa; Zainulabdeen, Khalid; Yousif, Emad; Mohamed, Safaa; Hairunisa, Nany; Bratovcic, Amra; Redwan, Amamer (Al-Nahrain Journal for Engineering Sciences, 2025)
Hydrogels are among the most versatile material classes used in biomedical applications. The material is of considerable interest in various fields of medicine due to its excellent features, such as high-water content, biocompatibility, and adjustable mechanical properties. The highlighted study thoroughly reviews Schiff-base thiadiazole-modified hydrogels as a novel functional material class, emphasizing their applicability in medical science. The addition of the Schiff-base and free thiazole groups to the hydrogel matrix introduces new antimicrobial activity, drug delivery, and bioadhesive attributes. An elaborate description of the methods employed to copolymerize thermoresponsive hydrogels with carbazole of thiadiazole as a binding group through free radical polymerization and visible light initiation is given under the first step of this general approach. The section on these hydrogels’ physical and chemical properties was then added with a bias on morphological characterization, water uptake studies, and mechanical properties of the materials. After that, the discussion on more applications commenced, and among these, the following sections study them in the field of life-saving biomedical devices such as wound healing, tissue engineering, delivery of drugs, and biosensing prepared biosensing. A key emphasis is given to those interaction modes between Schiff-base thiadiazole groups and the biological systems that fulfil the hydrogels’ healing mechanisms. These interaction modes, which include [specific modes], play a crucial role in the hydrogels’ healing mechanism. The mentioned scholarship, in addition, dwells on the issues and barriers of such materials and gives thorough and valid judgements about the present and future of the matter. This review and the hard evaluation provide a thorough insight into Schiff-base thiadiazole-modified hydrogels’ transformative impacts across the entire biomedicine area. A new approach is achieved by this review, in which the audience is made conscious and fully informed by presenting the most recent discoveries concerning the potential of Schiff-base thiadiazole-modified hydrogels to bring about innovative biomedical applications.